Carcass decontamination methods in slaughterhouses: a review - MILIOS (Κ. ΜΗΛΙΟΣ) K.; DROSINOS (Ε. ΔΡΟΣΙΝΟΣ) E. H.; ZOIOPOULOS (Π.Ε. ΖΩΪΟΠΟΥΛΟΣ) P. E. (Journal of the Hellenic Veterinary Medical Society, 2017)
European Union legislation approach to meat safety assurance advocates use of strict preventive hygiene measures and procedures to overcome threats by pathogens. Therefore, there is no need for carcass decontamination at the last stage of slaughtering process, using intervention methods. In contrast, the United States permit and regulate intervention decontamination methods. Generally, a HACCP system may use intervention treatments. These may be based solely on a non intervention system or use a combination of both. Interventions have the advantage of achieving a consistent reduction in bacterial contamination and require less manual input, but on the other hand, may also lead to carcass discolouration, produce large quantities of waste water and be relatively expensive. Moreover, intervention methods could constitute a means of concealing poor hygiene conditions during slaughtering or, even more, their residues could be a potential hazard for food safety. Non-intervention systems have the advantages of being relatively inexpensive, easy to implement and more preventive. However, these systems rely heavily on human effort and the possibility for error is considerably higher than the intervention systems. There are many carcass decontamination methods, as described in the relevant literature and used in slaughterhouses worldwide, such as: (i) cold/warm water washing, (ii) hot water washing, (iii) steam vacuuming, (iv) steam pasteurization, (v) irradiation, (vi) organic acid application, (vii) combination of organic acid application with other decontamination treatments and (viii) other chemical treatments. Aim of this review is to provide information on the relevant literature, as well as describe and Ncomment on the questions raised.